Sociocultural Determinants of Public Health - Utiuzh, I. G.; Sazanovych, L. V.; Утюж, Ірина Геннадіївна; Сазанович, Лариса Вікторівна (My University, 2022)
The article discusses public health in terms of national security, and socio-cultural aspects that influence its promotion. A complex socio-philosophical methodology underlies the findings analysis of social and medical surveys, national health-promoting lifestyle programs, television advertising content. The logically based approach of historical and philosophical parallelism allows discerning the path and outcome of current Ukrainians’ attitude toward health promotion. The study looks at several socio-cultural stages in the evolution of personal health attitudes as a moral concern and the foundation for public health promotion: the social transformations that the paternalistic model of medicine underwent, and the correlation between the individual and public health attitudes. The research of the personal health attitudes of Ukrainians demonstrates its deep embedment in religion and ideology. The current surveys have proved the emergence of a new tendency related to personal health – the recognition of health’s significance as a means of achieving productive wellbeing grounded on individual efforts regardless of governmental paternalism.
Keywords: healthcare; personal/public health promotion; sociocultural data; Christianity; Soviet ideology; State paternalism; national security